2022
DOI: 10.3389/fpain.2021.806310
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Differences in Pain Medication Usage and Healthcare Provider Utilization Among Adults With Chronic Low Back Pain

Abstract: Chronic low back pain (cLBP) is the most common reason for individual suffering and health care utilization in adults. Ample evidence suggests sociodemographic variables and socioeconomic status (SES) influence pain. However, a framework informing associations on race, SES, and the utilization of pharmacologic therapies and provider type are limited—particularly in cLBP. Thus, this study examined the extent to which sociodemographic (i.e., age, race, and gender) and socioeconomic factors (i.e., national area d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…In a study of Indianapolis, Phalen et al showed fentanyl-involved OODs rose from 15% in 2010 to 50% in 2017, concomitant with a shift from a younger White to a middle-aged Black demographic [9]. The lag between White and Black OOD peaks can be attributed to biased prescribing that promote unequal access to prescription opioids based on race or ethnicity, where young White women (and men) were more likely to receive opioids for pain management than Black counterparts of any age [14][15][16]. This trend of indiscriminate prescribing to Whites for emergency and surgical interventions, cancer treatment and/or pain management was referred to as the natural/semi-synthetic wave and involved mostly codeine, morphine, hydrocodone, and oxycodone abuse [17][18][19]).…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…In a study of Indianapolis, Phalen et al showed fentanyl-involved OODs rose from 15% in 2010 to 50% in 2017, concomitant with a shift from a younger White to a middle-aged Black demographic [9]. The lag between White and Black OOD peaks can be attributed to biased prescribing that promote unequal access to prescription opioids based on race or ethnicity, where young White women (and men) were more likely to receive opioids for pain management than Black counterparts of any age [14][15][16]. This trend of indiscriminate prescribing to Whites for emergency and surgical interventions, cancer treatment and/or pain management was referred to as the natural/semi-synthetic wave and involved mostly codeine, morphine, hydrocodone, and oxycodone abuse [17][18][19]).…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…However, we found that black participants had worse physical function, higher level of disability, and higher level of best pain in the past 24 hours compared with other races. Again, no studies were found for an MPS population, but in patients with low back pain, similar findings were reported in which Black participants also reported higher level of pain severity 51,55 and higher levels of disability compared to White participants, but the study did not find a gender difference in pain reporting. 55,56 Limitations of this study include a small sample size; thus, findings should be considered cautiously.…”
Section: Discussionmentioning
confidence: 48%
“…One study working with middle age patients found that more than 60% used pain medication for their low back pain. 51 Our study population is younger and reported lower levels of pain, yet a higher percentage of them used pain medications compared to the previously cited study population. Similar trends were also observed in an international population with musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 49%
“…Individual‐level socioenvironmental factors include factors such as education, income, marital status, insurance status, and number of people living in the household. Adults with greater socioenvironmental risk, that is, an income ≤$25,000, less than a high school education, no insurance or domestic partner, and/or unemployed experience more disabling pain compared to those with lower socioenvironmental risk (Allen‐Watts et al., 2021 ; Janevic et al., 2017 ; Mullins et al., 2022 ; Portenoy et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%